ANALISIS KARAKTERISTIK PERUSAHAAN TERHADAP CARBON EMISSION DISCLOSURE DAN PENGARUH CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN - Hanifah, Umi; , Dr. Fatchan Achyani, MSi; , Dr. Erma Setiawati MM, CA (2017)
This study aimed to analyze the effect of corporate's characteristics toward disclosure of carbon emission and effect disclosure of carbon emission toward firm value. Companies characteristics variable are proxied by corporate size, profitability and leverage. In this study, the sampling method is a company incorporated in the Jakarta Islamic Index (JII) which number of 34 companies. The data used in this study is the annual reports of each companies obtained through the Indonesia Stock Exchange and the hypotheses were tested using multiple regression analysis. The results of this study indicate that; 1) the leverage proven that is has significant negative effect toward disclosure of carbon emissions, while profitability and size of the company doesn't have significant influence, 2) the disclosure of carbon emissions are significantly influence the value of the company. Keywords: company size, profitability, leverage, carbon emission disclosure and corporate value.